PSYCHOLOGICAL THEORY OF POVERTY (Globalization and Business, 2018)
Poverty is one of the major problems that is faced by the modern society. The representatives of different fields of social science investigate poverty and develop their own perceptions regarding to the problem.Given paper investigates poverty in psychological theory because psychological factors like human behavior, decision-making and etc. could be considered as one of the most important aspects to staying poor.The development of psychological theories of poverty runs at least three periods: before 1980th psychologists were based on the individual specific of poverty explanations; in period from 1980 until 2000 the role of the individuals in poverty explanations were added by situational (social environmental) understanding of poverty existence, while after 2000 the psychologists extended the methodological boundaries of investigations and came to the multi-disciplinary understanding of poverty when acknowledged the impact of economic, political and social factors as roots of poverty.Despite the evolution of psychologists’ perspectives on the causes and roots of poverty, psychological theories of poverty are focused more on the individuals and their differences. Some of those theories, in particular Intelligence-based psychological theories, consider poverty as result of cognitive deficiencies. Other theories assume psychological sickness, psychological disturbance and moral deficiencies as a cause of poverty. For example, based on the Freud’s explanations of the ego as a part of the psyche that perceives the reality of the external world through assumption of conflict between inner and outer pressures, the psychological theories explain the poor’s dependence on the state in terms of character disorders of the welfare recipients and account this psychiatric deviation as the factor that keeps the poor in povertyThe article studied various theories of poverty such as:1)    Attribution Theory that is divided into internal and external attributions. Internal (dispositional) attribution explains human behavior by personal characteristic and possibilities of an individual, while an external (situational) attribution is based on the situational explanation of the human’s behavior;2)    “Depletable” self-control theory represents the conflicts between the aspirations and abilities of the human being;3)    Distancing theory which determines poverty as a psychological problem of separated classes.